2020
DOI: 10.1002/er.6033
|View full text |Cite
|
Sign up to set email alerts
|

Conceptual design and performance analysis of a novelCHPsystem integrated with solid oxide fuel cell and supercriticalCO2partial preheating cycle

Abstract: Summary The paper proposes a novel combined heating and power (CHP) system integrated with solid oxide fuel cell (SOFC) and supercritical CO2 (SCO2) partial preheating cycle to improve the energy utilization rate by employing the SCO2 cycle to recover the waste heat from the SOFC. The SCO2 partial preheating cycle can not only improve the net output power but also preheat the air supplied to the SOFC for enhancing the system efficiency. Sensitivity analysis is implemented to study the influences of six key par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…Due to the fact that CO 2 has a low critical temperature, a lower compression work can be obtained near the critical point, thus obtaining a higher efficiency. 8,9 So far, S-CO 2 cycle has been extended to solar energy, 10,11 fossil fuel, 12 fuel cell, 13 and geothermal energy. 14 In recent years, relevant researches have been intensively conducted, and various efficient cycle configurations including recuperated cycle, recompression cycle, and pre-compression cycle, have been constructed according to the characteristics of heat sources.…”
Section: Thermodynamic Cycles For Waste Heat Recoverymentioning
confidence: 99%
“…Due to the fact that CO 2 has a low critical temperature, a lower compression work can be obtained near the critical point, thus obtaining a higher efficiency. 8,9 So far, S-CO 2 cycle has been extended to solar energy, 10,11 fossil fuel, 12 fuel cell, 13 and geothermal energy. 14 In recent years, relevant researches have been intensively conducted, and various efficient cycle configurations including recuperated cycle, recompression cycle, and pre-compression cycle, have been constructed according to the characteristics of heat sources.…”
Section: Thermodynamic Cycles For Waste Heat Recoverymentioning
confidence: 99%
“…Huerta et al 13 evaluated the performance of a diesel pre‐reforming SOFC‐system with AOGR form an exergy perspective and concluded that optimum recirculation and low oxygen/carbon ratios led to relatively high system exergy efficiencies. Zhong et al 14 evaluated the performance of a novel SOFC‐based combined heat and power (CHP) system integrated with CO 2 partial preheating cycle. Applying an ejector to overcome the pressure drop, some part of the anode off‐gas was recycled and redirected to an external pre‐reformer.…”
Section: Introductionmentioning
confidence: 99%